Intervención psicopedagógica para la reeducación en el aprendizaje inicial de la lectura de una estudiante de 4to grado de la escuela municipal Dr. Ángel Felicísimo Rojas, 2023. - Bustamante Criollo, Josselyn Tatiana (2023)
The initial learning of reading is one of the fundamental tasks that are developed in the first years of basic education, however, many times children stage face difficulties in this process in the school. The main objective of this Curricular Integration Work was to implement the psycho-pedagogical intervention through the LOLE program for the reeducation in the initial learning of reading of a 4th grade student at Dr. Ángel Felicísimo Rojas Municipal School, 2023. A research was carried out under the mixed approach, with a case study method, descriptive and cross-sectional. The semi-structured interview applied to the teacher and the psycho-pedagogical form to the student's legal representative and the PECO test to the student were used. The results of the test for the evaluation of phonological knowledge (PECO) the student reached low levels in identification, addition, syllable and phonemic knowledge, except in the omission task where she reached a medium level, which is verified with the teacher's criteria; the findings of the execution of the LOLE program in the units destined to the tasks of identification of syllables and phonemes, addition and omission of syllables reached a valuation of achieved and in the units of addition and omission of phonemes is in a valuation in process. It is concluded that, of the problems presented initially, the student after the execution of the LOLE program, based on the results contrasted between the Pre-test and the Post-test, there is a decrease of errors in the phonological knowledge tasks, achieving a total score of 24 in the test, which corresponds to a high qualitative valuation. Keywords: reading, phonological awareness, identification, addition, omission.